Educação, filosofia e magia uma anarqueologia do cuidado de si entre o Daimon e os sonhos - Perencini, Tiago Brentam (Editora Oficina Universitária, 2020)
This book is a transversal investigation between the fields of education, philosophy and magic. Given the perception of the emergence of knowledge and practices of magic in the present time, I try to analyze the following problem: How does the relationship between philosophy and magic allow us to experience another philosophical education in the present time? My general objective is to develop approximate uses between magic and philosophy that problematize current practices in our academic training in philosophy. I experiment with the hypothesis that making visible the ethics of self-care in its archaic dimension - an emerging chronology of Western philosophy - allows an integration into the field of magic as a possibility of rehearsing a type of philosophical education that expands the set of techniques of the self beyond critical thinking and humanism as an epistemological and disciplinary paradigm that subjectifies us today. I think that self-care is linked to two key concepts related to it in the archaic period: the daimon and dreams. The specificity of my object invites Michel Foucault as the main interlocutor, but demands that I think with and beyond him. To do so, I test anarcheology as a research procedure and attitude, showing a certain (un)desirable interface between biopolitics and magic and also the gesture of erasing visionary thinking promoted by the secularized discourse of philosophy. Such a walk has enabled me to rehearse a philosophical education through gift, which integrates an ontology of the soul to the stylistics of existence through the ascetic and erotic dimension of self-care as a challenge for contemporaneity.